The United States : Japan Current Account Imbalance; A Review - Golub, Stephen (IMF Policy Discussion Papers; Policy Discussion Paper ;, 1994)
This paper reviews the macroeconomic and microeconomic dimensions of the United States-Japan conflict over trade. From a macroeconomic perspective, there is nothing surprising about Japan's surpluses, given global trends in saving and investment. The current accounts of the United States and Japan have both responded to exchange rate changes in a normal fashion with about a two-year lag. Although not the source of the Japanese current-account surplus, a key issue in the debate is the nature of Japanese trade policy and its possible effects on trade patterns. Empirical studies attempting to determine whether Japan's trade prices and quantities are abnormal have arrived at conflicting conclusions. This is a Paper on Policy Analysis and Assessment and the author(s) would welcome any comments on the present text. Citations should refer to a Paper on Policy Analysis and Assessment of the International Monetary Fund, mentioning the authors) and the date of issuance. The views expressed are those of the author(s) and do not necessarily represent those of the Fund.